Information Communication Technology (ICT): The New Frontier of Child and Youth Care (CYC) Practice - Bellefeuille, Gerard (Advances in Social Sciences Research Journal, 2020)
This exploratory course-based research investigates the use of information communication technologies (ICT) by child and youth care (CYC) students in their interactions with children, youth, and families. Data were collected through an online mixed closed- and open-ended survey. The data analysis consisted of a descriptive statistical analysis of the survey’s closed-ended questions and a thematic analysis of the survey’s open-ended questions. The findings revealed that CYC students are using ICT in their interactions with children, youth, and families and that the potential positive use of ICT should be addressed in a more significant way in the classroom.